2004
DOI: 10.1097/01.ju.0000131592.98562.16
|View full text |Cite
|
Sign up to set email alerts
|

Failure of a Monotherapy Strategy for Difficult Chronic Prostatitis/Chronic Pelvic Pain Syndrome

Abstract: Approximately a third of patients with treatment refractory CP/CPPS undergoing extensive evaluation and therapy based on a sequential monotherapy treatment strategy in a specialized prostatitis clinic had at least modest improvement in symptoms during 1 year. This study confirms that a treatment strategy based on the sequential application of monotherapies for patients with a long history of severe CP/CPPS remains relatively poor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(50 citation statements)
references
References 14 publications
0
48
0
2
Order By: Relevance
“…While the authors note that the NIH-CPSI was not designed as a diagnostic tool to evaluate treatment response, they do conclude that a step-wise, multimodal approach to therapy for long-standing CP/CPPS may be more effective than monotherapy protocols (48). A subsequent study involving the use of step-wise monotherapy strategy confirmed that patients with refractory CP/CPPS did show modest benefit as compared to monotherapy alone, but that the responses to this approach were still suboptimal, and instead multimodal, concurrent therapy would potentially be more appropriate (49).…”
Section: Treatment Approaches To Cp/cppsmentioning
confidence: 88%
“…While the authors note that the NIH-CPSI was not designed as a diagnostic tool to evaluate treatment response, they do conclude that a step-wise, multimodal approach to therapy for long-standing CP/CPPS may be more effective than monotherapy protocols (48). A subsequent study involving the use of step-wise monotherapy strategy confirmed that patients with refractory CP/CPPS did show modest benefit as compared to monotherapy alone, but that the responses to this approach were still suboptimal, and instead multimodal, concurrent therapy would potentially be more appropriate (49).…”
Section: Treatment Approaches To Cp/cppsmentioning
confidence: 88%
“…Studies addressing the capacity of Elocalcitol to induce CD4 ϩ CD25 ϩ regulatory T cells in EAP are currently in progress. The optimal medical treatment of CP/CPPS is not known (65), and effective therapies for CP/CPPS patients are warranted. Our results, showing that Elocalcitol interferes with key pathogenic events in already established autoimmune prostatitis, reducing by ϳ70% intraprostatic lymphomononuclear cell infiltration, indicate that treatment with this compound may inhibit prostatic inflammation in CP/CPPS patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other evidence suggests that pro-fibrotic effects of TGF-β may be partly mediated by CTGF [24]. As another potent profibrotic factor, CTGF is implicated in fibroblast proliferation, cellular adhesion, angiogenesis, and extracellular matrix (ECM) synthesis [25].…”
Section: Discussionmentioning
confidence: 99%